Answer:
Equation A = Graph 3
Equation B = Graph 4
Equation C = Graph 1
Equation D = Graph 2
Explanation:
The first equation is y = x² - 7x + 10
This equation can be rearranged as
![y = (x - (7)/(2) )^(2) - (9)/(4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jpll6brlhnln5v5sg9zhawxz0helrjsrbr.png)
![(y + (9)/(4)) = (x - (7)/(2))^(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ka606x4jq96vndfat673gu3x6563ue3gkm.png)
So, this is an equation of parabola having vertex at
and the axis is parallel to positive y-axis.
Therefore, graph 3 is correct for this equation A.
The second equation is y = (x - 4)(x + 2)
⇒ y = x² - 2x - 8 = (x - 1)² - 9
⇒ y + 9 = (x - 1)²
So,this is an equation of parabola, having vertex at (1,-9) and axis is parallel to positive y-axis.
Therefore, graph 4 is correct for this equation B.
Now, in equation C, y = (x - 4)² + 2, ⇒ y - 2 = (x - 4)²
This is also an equation of parabola having vertex at (4,2) and the axis is parallel to positive y-axis.
Therefore, graph 1 is correct for this equation C.
Now, the remaining equation D is of graph 2.
(Answer)